Infectious rhythm : metaphors of contagion and the spread of African culture - Browning, Barbara, 1961- (Routledge, 1998)
Barbara Browning follows the trail of ""infectious rhythm"" from the ecstatic percussion of a Brazilian carnival group to the eerily silent video image of the LAPD beating a man like a drum. Throughout, she identifies the metaphoric strain of contagion which both celebrates the diasporic spread of African culture, and serves as the justification for its brutal repression. The essays in this book examine both the vital and violent ways in which recent associations have been made between the AIDS pandemic and African diasporic cultural practices, including religious worship, music, dance.